Through their eyes : foreign correspondents in the United States - Hess, Stephen (Hess, Stephen. Newswork ;, 2005)
"Drawing on personal interviews and original survey research, reveals the mindset of foreign correspondents posted in the United States from a wide range of countries, and examines how foreign reporting has changed over the past 20 years"--Provided by publisher